The Effect of Thyroid Function on GDF15 Levels - Profili, Nicia I.; Fiorillo, Edoardo; Orrù, Valeria; Cucca, Francesco; Delitala, Alessandro P. (International journal of molecular sciences, 2025)
Growth differentiation factor 15 (GDF15) is a stress-response cytokine, which exerts different actions in physiological and pathological conditions. Thyroid disorders are common in the general population and their role on GDF15 levels has not been sufficiently addressed. Serum levels of GDF-15 and thyroid function were assessed in a large sample from the SardiNIA cohort (n = 4413). We further collected antibodies against thyroperoxidase and anti-thyroglobulin in all participants. Thyroid function correlated with GDF15. Specifically, after adjusting for covariates, thyrotropin had a positive association with GDF15, while free thyroxine was negatively correlated. We also found that subjects with circulating antibodies against thyroperoxidase had lower GDF15 levels. The reduced level of the thyroid hormone can cause a decreased metabolic activity and higher cell stress response, which, in turn, increases the production of GDF-15 as a defense mechanism. The association between antibodies against thyroperoxidase and GDF15 deserves additional study to elucidate the pathophysiologic relationship.